2022
DOI: 10.3390/ijms23137441
|View full text |Cite
|
Sign up to set email alerts
|

Codon Usage Provides Insights into the Adaptive Evolution of Mycoviruses in Their Associated Fungi Host

Abstract: Codon usage bias (CUB) could reflect co-evolutionary changes between viruses and hosts in contrast to plant and animal viruses, and the systematic analysis of codon usage among the mycoviruses that infect plant pathogenic fungi is limited. We performed an extensive analysis of codon usage patterns among 98 characterized RNA mycoviruses from eight phytopathogenic fungi. The GC and GC3s contents of mycoviruses have a wide variation from 29.35% to 64.62% and 24.32% to 97.13%, respectively. Mycoviral CUB is weak, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…All eight CpG-encompassing codons are found to be underrepresented in the Nipah virus [ 74 ]. RSCU values analysis of six codons containing TpA (TTA, CTA, ATA, GTA, TAT, and TAC) indicated that these are not preferred in Mycoviral genes [ 75 ]. HCV also showed a significant tendency to not prefer the codons with CpG or TpA dinucleotides [ 76 ], and many researchers have reported similar results [ 77 , 78 , 79 , 80 ] establishing a correlation between the presence of CpG and TpA and lower RSCU.…”
Section: Resultsmentioning
confidence: 99%
“…All eight CpG-encompassing codons are found to be underrepresented in the Nipah virus [ 74 ]. RSCU values analysis of six codons containing TpA (TTA, CTA, ATA, GTA, TAT, and TAC) indicated that these are not preferred in Mycoviral genes [ 75 ]. HCV also showed a significant tendency to not prefer the codons with CpG or TpA dinucleotides [ 76 ], and many researchers have reported similar results [ 77 , 78 , 79 , 80 ] establishing a correlation between the presence of CpG and TpA and lower RSCU.…”
Section: Resultsmentioning
confidence: 99%
“…The higher similarity of viral codon usage to the host can facilitate the replication of these pathogenic agents. The usage is similar to specific host genes [ 81 , 82 ] and is visible especially in viruses infecting a narrow spectrum of hosts [ 83 , 84 ]. Therefore, dynamic changes in codon usage in the hosts, e.g., due to changes in mutational pressure, can protect them against infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…dianthimycovirus 1, Heterobasidion partitivirus 13 strain an1, Phytophthora endornavirus 2 (PEV2), and PEV3 show that the high titer of mycoviruses can induce more severe symptoms in the host than mycoviruses with low titer [ 43 , 44 , 45 ]. Some researchers have hypothesized that hypovirulence-associated mycoviruses causing the hypovirulence of hosts result from the codon usage of mycovirus and host was similar which was beneficial to increase mycovirus accumulation [ 46 ]. In some cases that may be true, but here the codon usage was not the key reason.…”
Section: Discussionmentioning
confidence: 99%